POTENSI BAWANG MERAH (Allium cepa L) SEBAGAI ANTI DIABETES PADA PENELITIAN IN VIVO : Sebuah Tinjauan Systematic Review - Muhammad Rizalul Amzad (2020)
Deaths from diabetes continue to increase every year. Red onions are known to have the ability to reduce blood sugar levels in diabetics. This study aims to conclude various findings related to the potential ability of red onions as anti diabetes. Methods: This study uses Systematic Literature Review method using literatures from PubMed and DOAJ selected by PRISMA-P. Results: Red onion has strong hypoglycemic effect both in short or long-term administration due to the sulfur content in them. The improvement in glucose uptake in the liver comes from the antioxidant activity of quercetin from onions, but whole onions had better anti diabetes effect because of the synergistic effect of other phytochemicals. Red onion can reduce the level of oxidative stress and increase the ability of antioxidants due to the ability to neutralize free radicals by quercetin. Red onions have the ability to inhibit the increase in postprandial glucose levels by inhibiting alpha-glucosidase. Differences in parts that used and processing techniques can affect the anti diabetes ability of red onions. Conclusion: Red onions have anti diabetes abilities with different mechanisms that come from the synergistic effect of the phytochemicals in them.